2019
DOI: 10.3389/fpsyg.2019.01021
|View full text |Cite
|
Sign up to set email alerts
|

Biology Teachers’ Worldviews on the Global Distribution and Loss of Biodiversity: A GIS-Based Mental-Mapping Approach

Abstract: This paper explores (1) student teachers’ mental maps of the global distribution and loss of biodiversity and (2) their perception of threatened biodiversity at the national, transnational and global levels. Data was collected from a questionnaire study of student biology teachers from Germany ( n = 868) and Costa Rica ( n = 284). Student teachers’ mental maps matched quite well with the scientific view. Nevertheless, they clearly showed a “brazilisation bias,” mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Furthermore, Dikmenli's [30] investigation of biology student teachers showed that the important role of biodiversity in terms of SD often remains unrecognized. Compared to scientific data, secondary pre-service science teachers consistently overestimated the percentages of threatened plant species on different spatial levels (national, transnational, and global) [33]. However, knowledge about highly complex SD challenges, like biodiversity loss and climate change, represents a key requirement for ESD.…”
Section: Student Teachers' Knowledge Of Sd-related Topicsmentioning
confidence: 87%
See 4 more Smart Citations
“…Furthermore, Dikmenli's [30] investigation of biology student teachers showed that the important role of biodiversity in terms of SD often remains unrecognized. Compared to scientific data, secondary pre-service science teachers consistently overestimated the percentages of threatened plant species on different spatial levels (national, transnational, and global) [33]. However, knowledge about highly complex SD challenges, like biodiversity loss and climate change, represents a key requirement for ESD.…”
Section: Student Teachers' Knowledge Of Sd-related Topicsmentioning
confidence: 87%
“…Furthermore, science teachers in the US were unaware of the extent of scientific consensus about anthropogenic climate change [28]. Concerning biodiversity, previous research suggests that science teachers possess insufficient knowledge [30][31][32][33][34]. British, German, Cypriot, and Swiss student teachers were often found to be not familiar with the term "biodiversity" [31].…”
Section: Student Teachers' Knowledge Of Sd-related Topicsmentioning
confidence: 99%
See 3 more Smart Citations